Absorpční kapacita strukturálních fondů (2007-2013): typologie českých mikroregionů - Hájek, Oldřich; Novosák, Jiří; Horváth, Peter; Novosáková, Jana (Univerzita Pardubice, 2017)
The intent of this paper was to suggest a typology of Czech microregions based on the demand side of their structural funds (SF) absorption capacity in the programming period 2007-2013. Moreover, the demand side of SF absorption capacity of the so called microregions with concentrated state support was evaluated. Concerning the first intent of this paper, seven clusters of microregions were defined, using a new approach based on the following theoretically substantiated variables for operationalizing the demand side of SF absorption capacity – the number of project applications submitted for financing by SF, the amount of SF requested for one project application, and the share of project applications supported by SF. The relevance of these clusters was shown by the associations between their absorption capacity on the demand side and relative SF allocation. Concerning the second intent of this paper, it was shown that the so called microregions with concentrated state support are less likely to have high absorption capacity on the demand side compared with their not supported counterparts.
Absorption capacity of structural funds (2007-2013): typology of Czech microregions
Keywords: absorption capacity; structural funds; cluster analysis; Czech Republic; O18; O22; R12; R58